Bioactivity of hydroxyapatite/montmorillonite clay nanocomposite - Nawang, Rosnah; Hussein, Mohd Zobir; Matori, Khamirul Amin; Che Abdullah, Che Azurahanim; Hashim, Mansor; Osman, Rosiah (2018)
In-vitro bioactivity behavior of hydroxyapatite (HA)/montmorillonite (MMT) nanocomposite was studied by immersing the samples in a phosphate buffer solution. The weight changes before and after the testing were recorded and the morphology of the samples was studied. Results showed that a significant weight loss occured in nanocomposite with the ratio of HA:MMT 50:50. The morphology of the sample revealed the apatite formation on the surface of the nanocomposite which suggested the potential use of the material for bone implant application.